MORPHOFUNCTIONAL CHANGES IN THE PLACENTA AND EXPRESSION OF THE ENDOTHELIAL MARKER CD34+ IN PREGNANT WOMEN WITH TYPE 1 AND 2 DIABETES MELLITUS - Dudareva, Yulia Alekseevna; Seroshtanova, Daria Nikolaevna; Pesotskaya, Anastasia Valentinovna (Mother and Baby in Kuzbass, 2026)
Despite significant advances in the care of pregnant women with type 1 and type 2 diabetes and the prevention of obstetric complications, perinatal morbidity and mortality remain a pressing issue.The aim – of this study was to investigate morphofunctional changes in the placenta and the expression of the endothelial marker CD34+ in pregnant women with type 1 and type 2 diabetes and to establish a relationship with cytokine levels (IL-6, IL-8, IL-10) as predictors of perinatal complications.Materials and Methods. This prospective, comparative, case-control study included an analysis of pregnancy outcomes in 41 women with diabetes mellitus, including type 1 – 22, type 2 – 19. The control group included 24 women with normal pregnancy and delivery without carbohydrate metabolism disorders. This included an assessment of pregnancy progression and perinatal outcomes, analysis of serum IL-6, IL-8, and IL-10 cytokine levels at 30,0-35,0 weeks of gestation, and pathological and immunohistochemical examination of the placenta, including determination of the endothelial marker CD34+.Results and Discussion. Women with diabetes mellitus and perinatal complications had chronic subcompensated placental insufficiency, compared to the control group (100,0% and 8,3%, respectively, p = 0,001). Threshold concentrations of IL-10 in women with type 1 diabetes mellitus in the blood serum have been established, so a level of ≥ 3,0 pg/ml (RR = 4,79; p = 0,0002) increases the risk of perinatal complications, while in pregnant women with type 2 diabetes mellitus, significant predictors were IL-6 ≥ 1.8 pg/ml (RR = 5,04; p = 0,017), IL-8 ≥ 7,0 pg/ml (RR = 2,32; p = 0,0136), IL-10 ≥ 3.0 pg/ml (RR = 10,12; p = 0,0007). A relationship was revealed between morphological changes in the placenta, immunohistochemical study using the endothelial marker CD34+, the content of pro- and anti-inflammatory cytokines in the blood serum and clinical manifestations Placental disorders in women with pregestational diabetes mellitus.Conclusion. Patients with pregestational diabetes mellitus require a multidisciplinary approach, beginning with pregnancy planning, risk stratification, and step-by-step prediction of perinatal complications and adverse outcomes. This approach aims to determine appropriate management strategies and the timing and mode of delivery, which in turn will help determine the path to improving perinatal outcomes.
Keywords: pregestational diabetes mellitus; CD34+; perinatal complications; endothelial dysfunction; placenta